Management, markets and democracy: Australian local government reform in the 1990s - Neil, Marshall; Dollery, Brian; Witherby, Angus (1999)
Australian local government has been subjected to extensive reform during the 1990s. This article considers the three main dimensions of the reforms - changes to management structures, the introduction of competition policy, and municipal consolidation. It reviews the evidence available about the nature of outcomes and examines the impact of the reforms on governance values. It is argued that, so far, economic considerations have been balanced by a commitment to community participation. Recent political developments, however, may yet prove to be an emerging threat. - Reproduced
Keywords: Democracy - Australia; Management - Australia; Local government - Australia; Local government